Reasons for the growth of destructive fear during the transformation of individual components of actual self-perception - M. M. Basimov (Вестник университета, 2023)
The article presents a causal view on the influence that components of the actual self-perception, “Suppressed – independent” and “Indifferent (indifferent) – included,” have on the transformation of destructive fear in a stressful life situation. None of the coefficients of linear correlation between the indicator of destructive fear and the components of actual self-perception exceed 0.25 in absolute value; they are too weak to be noted. However, in the model for quarts of the independent variable, two strong relationships were found through the use of the author’s method, showing the non-linear nature of destructive fear. Linear models are unacceptable in this case, since they can only distort the results extremely and lead to erroneous conclusions and interpretations. The author of the article provides descriptions of these dependencies as well as their visual graphical representation and explains in what way they would most likely be assessed using the traditional approach.